(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
Introduction: The COVID-19 health situation has raised interest in identifying the impact on the mental health of older adults due to the susceptibility to abundant and false information that emerges from the media, which generates the phenomenon known as "infodemic". Objective: To analyze the relationship between the infodemic on COVID-19 and its impact on the mental health of older adults. Methodology: Mixed study with an explicit sequential strategy, instruments used in 292 older adults: Geriatric Depression Scale and Geriatric Anxiety Inventory. Carried out in two phases: the first phase collected information from older adults through the forms platform, for the analysis, inferential statistics were used with the help of Excel and SPSS programs, and the correlation of variables was performed, and the second phase involved a qualitative study. Results: It was identified that the greater the exposure to information about COVID-19 through the media, the more depression and anxiety are manifested in older adults, with a P-value = .000, a significant data, gender origin studies. Conclusions: Health crises affect the mental health of older adults, impacting various resources, it is crucial to understand these repercussions to implement mitigation strategies, improving the quality and veracity of information through public policies and communication, to protect their mental health in future crises.